<u>Answer;</u>
<em>Spring constant </em>
<u>Explanation;</u>
The measure of a spring’s resistance to being compressed or stretched is the <u>spring constant</u>.
- The symbol of spring constant is K, since it is a constant. From the Hooke's law,for a helical spring or any elastic material, the extension force is directly proportional to the extension provided the elastic limit is not exceeded.
- Therefore; the spring constant = Force/extension. That is; K = F/e; where k is the spring constant, F is the extension force and e is the extension.
- Spring constant depicts the resistance of the spring to compressional and stretching forces.
1) science does not accept personal story's as evidence, pseudoscience relies on these story's as evidence.
2) science argues from scientific knowledge, pseudoscience argues from ignorance
3) science progresses, pseudoscience does not progress
and 4) (just in case) science holds pier review, pseudoscience does not
Answer:
if one wave has a negative displacement, the displacements would be opposite each other, so the displacement where the waves overlap is less than it would be due to either of the waves separately.
-causes a moment where the net displacement of the medium is zero. energy of waves hasn't vanished, but it is in the form of the kinetic energy of the medium
-then both emerge unchanged
Explanation:
To find the tangent plane to the surface f(x,y,z)=0 at a point (X,Y,Z) we use the following method:
<span>Calculate grad f = (f_x, f_y, f_z). The normal vector to the surface at the point (X,Y,Z) is grad f(X,Y,Z). The equation of a plane with normal vector n which passes through the point p is (r-p).n=0, where r=(x,y,z) is the position vector. So the equation of the tangent plane to the surface through the point (X,Y,Z) is ((x,y,z)-(X,Y,Z)).grad f(X,Y,Z)=0. </span>
<span>Now in your case we have f(x,y,z)=y-x^2-z^2, so grad f=(-2x,1,-2z), and the equation of the tangent plane at the point (X,Y,Z) is </span>
<span>((x,y,z)-(X,Y,Z)).(-2X,1,-2Z)=0, </span>
<span>that is </span>
<span>-2X(x-X)+1(y-Y)-2Z(z-Z)=0, </span>
<span>i.e. </span>
<span>-2Xx+y-2Zz = -2X^2+Y-2Z^2. (1) </span>
<span>Now compare this equation with the plane </span>
<span>x + 2y + 3z = 1. (2) </span>
<span>The two planes a_1x+b_1y+c_1z=d_1, a_2x+b_2y+c_2z=d_2 are parallel when (a_1,b_1,c_1) is a multiple of (a_2,b_2,c_2). So the two planes (1),(2) are parallel when (-2X,1,-2Z) is a multiple of (1,2,3), and we have </span>
<span>(-2X,1,-2Z)=1/2(1,2,3) </span>
<span>for X=-1/4 and Z=-3/4. On the paraboloid the corresponding y coordinate is Y=X^2+Z^2=1^4+9^4=5/2. </span>
<span>So the tangent plane to the given paraboloid at the point (-1/4,5/2,-3/4) is parallel to the given plane.</span>
In the system described above we will have four forces that is acting on the puck. These are the weight, the normal force, the frictional force, and the force applied by the player. To determine the force applied by the player, we need to calculate first for the frictional force which is equal to the product of the coefficient of friction and the normal force. We do as follows:
Summation of forces in the y-direction:
W = Fn
Fn = 1.70 N
Summation of force in the x-direction
F = Fr = 0.06Fn
F = 0.06 (1.70) = 0.102 N